2018
DOI: 10.1016/j.jacc.2018.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental Vitamins and Minerals for CVD Prevention and Treatment

Abstract: The authors identified individual randomized controlled trials from previous meta-analyses and additional searches, and then performed meta-analyses on cardiovascular disease outcomes and all-cause mortality. The authors assessed publications from 2012, both before and including the U.S. Preventive Service Task Force review. Their systematic reviews and meta-analyses showed generally moderate- or low-quality evidence for preventive benefits (folic acid for total cardiovascular disease, folic acid and B-vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(152 citation statements)
references
References 81 publications
5
128
0
19
Order By: Relevance
“…Improved diet quality is associated with reduced all‐cause mortality. whereas multivitamin and multimineral supplements may not improve life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…Improved diet quality is associated with reduced all‐cause mortality. whereas multivitamin and multimineral supplements may not improve life expectancy.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study with Korean men, the authors found that higher dietary intake levels of vitamin B6 were associated with a reduced CVD risk [165]. Vitamin B3 might increase all-cause mortality, which was probably associated with its adverse effects on glycemic response [166,167].…”
Section: Vitamin B-complex and Microbiotamentioning
confidence: 99%
“…The most popular mechanism of action proposed for (poly)phenols is based on their antioxidant properties. However, provision of antioxidants actually increases cancer risk (Jenkins et al, ), and the exact role of oxidative stress (now called redox code; Jones & Sies, ; and never fully elucidated in humans) in cancer aetiology is, to date, still elusive. Conceivably, modulation of the redox code by (poly)phenols (including OOPC) might play some roles in cancer and progression of cancer stem cells, as well as adjunct therapy (Ritter & Greten, ).…”
Section: Pharmacological and Nutraceutical Properties Of Htmentioning
confidence: 99%
“…The most popular mechanism of action proposed for (poly)phenols is based on their antioxidant properties. However, provision of antioxidants actually increases cancer risk (Jenkins et al, 2018), and the exact role of oxidative stress (now called redox code;…”
Section: Chemopreventionmentioning
confidence: 99%